Beneficial effects of atorvastatin on sex‐specific cognitive impairment induced by a cerebral microhaemorrhage in mice. (8th March 2021) - Bergeron, Sandrine; Barus, Romain; Leboullenger, Clémence; Auger, Florent; Bongiovanni, Antonino; Tardivel, Meryem; Jonneaux, Aurélie; Laloux, Charlotte; Potey, Camille; Bordet, Régis; Chen, Yaohua; Gautier, Sophie
Abstract : Background and Purposes: Cerebral microhaemorrhages (CMHs) are associated with cognitive decline in humans. In rodents, CMHs induces cognitive impairment in male mice along with sex‐specific cortical and hippocampal changes affecting neural, glial and vascular functions. Statins, have been proposed to prevent cognitive decline. We tested here the action of atorvastatin on CMH‐induced cognitive impairment in a murine model of CMH. Experimental Approach: Using a multimodal approach combining behavioural tests, in vivo imaging, biochemistry and molecular biology, the effects of oral administration of atorvastatin on the sex‐specific changes induced by a cortical CMH were studied in male and female mice (C57BL/6J) at 6‐week post‐induction using a collagenase‐induced model. Key Results: Atorvastatin caused specific effects according to the sex‐specific CMH‐induced changes. In males, atorvastatin improved the visuospatial memory, induced a local modulation of microglial response and enhanced brain‐derived neurotrophic factor (BDNF)‐tropomyosin receptor kinase B (trkB) and vascular endothelial growth factor (VEGF) expression in the cortex. In the hippocampus, atorvastatin increased glucose metabolism and modulated astrocytes morphology. In females, atorvastatin did not modulate visuospatial memory despite the increased expression of cortical BDNF and the decrease in the number of hippocampal astrocytes. Atorvastatin also induced a decrease in the expression of cortical oestrogen receptors but did not modify body weight nor serum cholesterol levels in both sexes. Conclusion and Implications: Atorvastatin modulated the sex‐specific cognitive impairment induced by the CMH with a pathophysiological impact mainly within the cortical area. It could represent a promising candidate for future sex‐stratified clinical trials in patients with CMH.